Self-accommodating martensite plate variants in shape memory CuAlNi alloys - Aydogdu, Y; Aydogdu, A; Adiguzel, O (Elsevier Science Sa, 2002)
In noble metal copper-based beta-phase alloys, which exhibit the shape memory effect. martensitic transformation occurs by lattice invariant shears on close-packed {1 1 0}(beta) planes of the matrix, called the basal plane of the martensite. The parent single crystal undergoes the martensitic transformation on cooling in a self-accommodating manner minimising the total shape change at the advanced stage of the transformation. These alloys are deformed by variant-to-variant transformation when stressed in the martensite state. The reversible shape memory effect is also considered in terms of the correspondence-variants and the formation of each martensite is accompanied by a definite shape deformation. The so-called self-accommodation is achieved by combining suitable correspondence-variants. In a single crystal of the parent phase. 24 martensite variants grouped around six {1 1 0}(beta) planes can be formed at temperatures lower than M,. In the present study, configurations of the martensite variants in CuAlNi alloys have been investigated by an electron microscope technique. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: self-accommodation; martensite plate variants; CuAlNi alloys; shape memory effect